Local people's views on the evidence-based skilled-maternal-care in Mfuwe, Zambia: a qualitative study - Choolwe Muzyamba (BMC, 2019)
Abstract Background There is growing demand for high quality evidence-based practice in the fight against negative maternal health outcomes in Sub-Saharan Africa (SSA). Zambia is one of the countries that has transposed this evidence-based approach by outlawing Traditional Birth Attendants (TBAs) and recommending exclusive skilled-care. There is division among scholars regarding the usefulness of this approach to maternal health in SSA in general. One strand of scholars praises the approach and the other criticizes it. However, there is still lack of evidence to legitimize either of the two positions in poor-settings. Thus the aim of this study is to fill this gap by investigating local people's views on the evidence-based practice in the form of skilled-maternal-care in Zambia, by using Mfuwe as a case study. Methods With the help of the Social Representation theory, Focus Group Discussions (FGDs) were conducted in Mfuwe, Zambia with 63 participants. Findings The study shows that the evidence-based strategy (of exclusive skilled-care) led to improved quality of care in cases where it was accessible. However, not all women had access to skilled-care; thus the act of outlawing the only alternative form of care (TBAs) seemed to have been counterproductive in the context of Mfuwe. The study therefore demonstrates that incorporating TBAs rather than obscuring them may offer an opportunity for improving their potential benefits and minimizing their limitations thereby increasing access and quality of care to women of Mfuwe. Conclusion This study illustrates that while evidence-based strategies remain useful in improving maternal care, they need to be carefully appropriated in poor settings in order to increase access and quality of care.